Peak-Forming-Enhanced Electromagnetic Imaging Method for Implantable Device Localization - Anzai, Daisuke; Kobayashi, Hisato; Hyry, Jaakko; Kobayashi, Takumi; Kirchner, Jens; Fischer, Georg (IEEE Access, 2024)
To improve the quality of medical treatment using implantable devices, accurate location information for implantable devices must be acquired and reliable implant communications for vital data transmission must be ensured. This paper focuses on an electromagnetic (EM) imaging-based method using scattered EM fields, which enables implant device localization without requiring any information regarding the human body structure. However, in conventional EM imaging-based methods, it is difficult to accurately estimate the capsule location at high frequencies because of significant signal attenuation. Herein, we propose an EM imaging-based localization method enhanced by peak-formed incident electric fields generated by overlaying multiple EM waves. Our proposed method utilizes information regarding scattered electric fields by sweeping the peak location without increasing the measurement points. The performance improvement by the proposed method was evaluated in two- and three-dimensional computer simulations such that the proposed EM imaging-based localization can be further optimized to achieve precise estimation accuracy at a high frequency of 2.4 GHz.
CRIS-Team Scopus Importer:2024-12-06
Keywords: EM imaging; Implantable medical device; peak forming; scattered electric field